2021
DOI: 10.1002/cite.202000174
|View full text |Cite
|
Sign up to set email alerts
|

Methanol‐to‐Olefins Reaction over Large‐Pore Zeolites: Impact of Pore Structure on Catalytic Performance

Abstract: In the methanol-to-olefins (MTO) reaction, product flexibility is important for meeting the fluctuating chemicals demands. In this paper, the catalytic performance of recently reported zeolites having 12-ring pores, such as boroaluminosilicate CON-type zeolite ([Al,B]-CON), MCM-68, and YNU-5 zeolites, in the MTO reaction was compared to understand the relationship between zeolite framework and product selectivity. The catalytic performance of the synthesized zeolites was compared with that of Beta, mordenite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…The observed size differences in the particle morphologies of the The XRD patterns of the H + -form samples are shown in Figure 1. For the samples without CTAB in the mother gel (Figure 1b−e), peak patterns almost identical to those of the CON-type zeolites 9,32,33,[36][37][38]40 were obtained, except for Si/ Al = 100 (Figure 1a). The formation of [Al, B]-CON-100 with a CON-type phase was not observed under the conditions applied in this study, suggesting that the synthetic window of the Si/Al molar ratio for the CON-type boroaluminosilicate zeolite ranges from ca.…”
Section: ■ Experimental Sectionmentioning
confidence: 65%
See 2 more Smart Citations
“…The observed size differences in the particle morphologies of the The XRD patterns of the H + -form samples are shown in Figure 1. For the samples without CTAB in the mother gel (Figure 1b−e), peak patterns almost identical to those of the CON-type zeolites 9,32,33,[36][37][38]40 were obtained, except for Si/ Al = 100 (Figure 1a). The formation of [Al, B]-CON-100 with a CON-type phase was not observed under the conditions applied in this study, suggesting that the synthetic window of the Si/Al molar ratio for the CON-type boroaluminosilicate zeolite ranges from ca.…”
Section: ■ Experimental Sectionmentioning
confidence: 65%
“…The introduction of seed crystals into a synthetic gel is one of the most effective ways to promote crystallization kinetics that favor the formation of the desired zeolite crystal topology and size . As it is widely known that 12MR pore structures are topologically equivalent to those of CON phases, zeolite beta (*BEA) has been used as seeds in the synthesis of CON-type zeolite materials in several reports. ,,, , Previously, Okubo and co-workers reported the considerable influence of the seed crystals CIT-1­(CON) and beta (*BEA) on the formation of CON-type zeolites and their crystal sizes, where 20 wt % of seed crystals relative to the silica source and tetraethylammonium hydroxide were used . This aroused our interest in the influence of the seed crystal on the formation of CON-type zeolites in the traditional synthetic method using 2 wt % of seeds and TMMAOH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Davis group examined the selectivity of a large number of small-pore cage-type topologies and found that the olefin selectivity was quite well correlated with the cage-defining ring size, which is the critical diameter of the ellipse that can be inscribed in the cage (Figure ). The zeolites with the smallest cage-defining ring size had the highest selectivity to ethene versus propene, while very large cages produced longer olefins …”
Section: Methanol To Olefins Reactionsmentioning
confidence: 99%
“…Owing to their high accessibility and diffusibility by large pores, as well as superior selectivity due to medium pores, a CON-type zeolite is expected to be a promising catalyst, especially for the methanol-to-olefins (MTO) reaction, which is considered a clean alternative path to produce light olefins. , An aluminoborosilicate CON-type zeolite, which can be prepared by both postsynthetic modification and direct synthesis to introduce acid sites generated by framework aluminum, has exhibited excellent catalytic performances. Unlike typical zeolites such as ZSM-5, SAPO-34, mordenite, and beta, CON-type zeolites have demonstrated a long catalytic lifetime and high selectivity for key plastic feedstocks such as propylene and butane . However, two significant problems hinder the utilization of CON-type zeolite: (i) a long synthesis duration (7 days) and (ii) a highly expensive OSDA with a complex structure ( N , N , N -trimethyl-(−)- cis -myrtanylammonium (TMMAOH)).…”
Section: Introductionmentioning
confidence: 99%